ANALISIS MISKONSEPSI SISWA MELALUI TES MULTIPLE CHOICE MENGGUNAKAN CERTAINTY OF RESPONSE INDEX PADA MATA PELAJARAN FISIKA MAN 1 BUKITTINGGI - Hafizah, Deni; Haris, Venny; Eliwatis, Eliwatis (Jurnal Pembelajaran MIPA, 2014)
Students ability are low to understands physics concept that cause misconceptions incorrectly concept. In the effort tackling student misconceptions, earlier have among been differentiated student which misconceptions, know concept and lack of knowledge by using CRI (Certainty of Response is Index) method. To the effect this research to analyze student misconceptions and what material that misconceptions happens. Student of X.2 and X.3 MAN 1 Bukittinggi that will be analyzed misconceptions by give test multiple choiceÂ  with reasoningÂ  end as much 30 problems and will be analyzed by using CRI method. Result of research to point out misconceptions that happening high enough. Highest of misconceptions is influence heat for change to form object.Key words: misconceptions, CRI (Certainty of Response is Index)